Isoterm Biosorpsi Ion Logam Cu2+ Dengan Menggunakan Limbah Spent Mushroom Substrate (SMS) Sebagai Biosorben - Martin, Dicky; Yenie, Elvi; Daud, Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Spent Mushroom Substrate (SMS) or remaining mushroom media is agro-residue and the remaining mesillium fungus after harvesting mushroom. SMS has several types of polymers such as lignin, cellulose and hemiselulose degraded by mycelium due to the fungal growth process which is then converted into simpler molecules to use as biosorbent that can be used to set aside Cu metals. The purpose of this study was to determine the model of metal adsorption isoterm pattern Cu2+. Keywords: Adsorption, ions Cu2+, Spent Mushroom Substrate (SMS), Isoterm, Biosorbent